(untitled) (Terr@ Plural, 2023)
The objective of the research is to analyze the dynamics of deforestation in the Agroextractive Settlement Project (PAE) Porto Rico. For the development of the study, it was necessary: a) to perform the temporal-spatial cut of the place to be studied; b) survey of bibliographic and documentary data; c) construction of a cartographic database with mapping of the site over the last 30 years; d) on-site visit to observe potential changes with primary data collection and construction of a photograph bank. The settlement in question is located in the state of Acre and is environmentally differentiated - it is intended to develop economically while respecting local environmental characteristics and its population has an agro-extractivist way of life. There has been an increase in deforestation over the last few years, subdivision of lots, and territorial conflicts. The nuances of this type of management are important to be analyzed as a way to improve public policies that minimize possible impacts on the natural environment, especially deforestation.